PEMURNIAN DAN KARAKTERISTIK DEXTRANASE BACTEROIDES RUMINICOLA SUBSP BREVIS - Tami ldiyanti (Jurnal Kimia Terapan Indonesia, 1994)
The dextranase of B.ruminicola subsp. brevis from bovine rumen has high ability to degrade the D - (1,6) a-glucosidic linkages of dextran substrate. Purification of crude dextranase was done by using ion-exchange chromatography and electrophoresis. It was observed that the purification until ion exchange step by microcrystal cellulose column increased theactivity of dextranase by 400 fold. The purified dextranase was most active at pH 5.5 and 40°C-45°C. The enzyme was strongly inhibited by metal ions such as Cu++,Fe++ and Hg++. The major product in early stage of dextran hydrolysis which were analyzed by paper chromatography showed dextranase of B.ruminicola to be an endotype enzyme.